Characterization of Al/Cu 3BiS 3/buffer/ZnO solar cells structure by TEM (2012)
This work presents results from a study carried out on the Al/Cu3BiS3/Buffer/ZnO stacked layer, using high-resolution transmission electron microscopy (HRTEM). This system is used to fabricate solar cells with Al/Cu3BiS3/In2S3/ZnO and Al/Cu3BiS3/ZnS/ZnO structures. The conforming layers function as electrical contact, absorber layer, buffer layer, and optical window, respectively. The detailed results of Cu3BiS3 thin film investigation by HRTEM are presented. The Cu3BiS3 thin films are non-homogeneous and are strongly dependent on deposition conditions with grain size between 6.5 and 20 nm showing a nano-crystalline character. We found that the buffer layer of In2S3 grows in a polycrystalline structure, whereas the layer of ZnS reveals an amorphous structure. The performed study of these solar cells gives us significant information about their crystalline structure and allows us to visualize each of the constituting layers as well as of the Al/Cu3BiS3, Cu3BiS3/buffer, and buffer/ZnO interfaces. This study was correlated with electrical properties.